Financial Inclusion Among Women Through FinTech in Pokhara - Acharya, Pooja; Kunwar, Kripa; G.C., Surya Bahadur (Journal of Interdisciplinary Studies, 2025)
Financial inclusion creates opportunities for women’s economic participation. The aim of the study is to examine the impact of Fintech adoption on financial inclusion among women. Hence this study used a convenience sampling method to collect data form 216 respondents. Descriptive as well as causal research design was employed to conduct the study. Multiple regression analysis revealed that facilitating conditions, effort expectancy, and personal innovativeness determined the intention to use FinTech among women. In addition, FinTech adoption can be a catalyst to improve financial inclusion among women. The study also claims the partial mediation of actual use of FinTech in the relationship between intention to use FinTech and financial inclusion. The study offers valuable insights for policymakers and financial institutions regarding the association between Fintech and financial inclusion.